The Influence of Services Quality to Domestic Tourists’ Loyalty through Domestic Tourists’ Satisfaction at Mount Bromo Tourism in East Java Indonesia - Amelia, Rizki; Palupi, Santi (E-Journal of Tourism; Volume 3 Number 2 (September 2016), 2016)
This study was aimed to analyze the influence of quality of tour services to domestic tourists’ loyalty at Mount Bromo East Java. The number of respondents were 100 domestic tourists who have visited Mount Bromo at least 2 times. Three variables were used namely, quality of service as an independent variable, satisfaction as an intervening variable, and loyalty as the dependent variable. Path analysis was used to analyze the data. The results showed that: i) Quality of tour services significantly influenced satisfaction of domestic tourists at Mount Bromo, ii) Quality of tour services also significantly influenced domestic tourists’ loyalty, and iii) Customers satisfaction significantly influenced domestic tourists’ loyalty at Mount Bromo. The results indicated that there were positive perception of domestic tourists on the quality of tour services, satisfaction and loyalty at Mount Bromo.
Keywords: quality of services; domestic tourists; satisfaction; loyalty